Green innovation effects and energy efficiency enhancement of China’s innovative industrial cluster pilot policies: evidence from 281 cities - Zhou, Pinglu; Ning, Xiaoya (Frontiers in Energy Research, 2025)
National innovative industrial clusters serve as pivotal platforms for technological innovation and play a vital role in advancing urban green technological innovation (GTI). This study empirically examines the impact of the pilot innovative industrial cluster policy on urban GTI using panel data from 281 prefecture-level cities in China (2006–2021), employing a difference-in-differences (DID) model that treats the policy as a quasi-natural experiment. The findings reveal that the pilot policy has significantly catalyzed urban GTI, a conclusion that remains robust after a series of robustness tests. Heterogeneity analysis indicates that the promotional effect is more pronounced in eastern and western cities, as well as in cities with high environmental concern and strong intellectual property protection (IPP). Mechanism analysis demonstrates that the policy drives GTI primarily through three channels: enhancing entrepreneurial activity, agglomerating scientific and technological talent, and increasing financial and scientific investment. Furthermore, the policy significantly improves urban energy utilization efficiency, with GTI acting as a critical mediating mechanism. These findings provide valuable empirical evidence and strategic insights for policymakers to refine the cluster policy and foster sustainable urban development towards achieving the dual-carbon goals.